PERCEPTIONS OF POST GRADUATE STUDENTS ON FLIPPED CLASSROOM (Journal of Pharmaceutical Negative Results, 2022)
Flipped classroom, as an innovative strategy used in higher education, suits the demands of students at a university level, developing their critical thinking and problem-solving skills. This study examined the perceptions of post graduate students of X University on flipped learning system with respect to gender the stream of education, locale and course of study. The sample of the study consisted of 892 post graduate students, randomly chosen from all the departments of basic science, social science and professional courses of X University. A self-made questionnaire used in order to identify the perceptions of students towards flipped classroom. The analytical descriptive approach was used in this study. Mean, standard deviation, t-test, and One-way-ANOVA were used to analysis data. The present study showed that the post graduate students’ perceptions of flipped classroom in the X university were high. This study recommended the necessity of using flipped learning technique at different departments of X university due to its efficiency in developing students’ understanding of the curriculum and in motivating them to become active rather than passive participants in the classroom.